Area Postrema Syndrome: A Rare Feature of Chronic Lymphocytic Inflammation With Pontine Perivascular Enhancement Responsive to Steroids - Zhang, Weihe; Cui, Lei; Dong, Mingrui; Tian, Zhaohui; Jiao, Yujuan; Jiao, Jinsong (Frontiers in Neurology, 2020)
Background: The area postrema syndrome (APS) is a unique diagnostic criterion for neuromyelitis optica spectrum disorders (NMOSD). However, APS has rarely been reported in cases of chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids (CLIPPERS). Case presentation: A 36-year-old woman presented with APS and clinical features of diffuse central nervous system involvement during the early stage of the disease. Owing to the absence of serum aquaporin 4 antibodies, she was initially misdiagnosed as a case of seronegative NMOSD. However, the distinct neuroimaging characteristics (symmetrical small punctuate gadolinium enhancing lesions [pepper-like]), typical clinical/radiological relapse, and intense steroid-dependence in this case, prompted us to correct the diagnosis as probable CLIPPERS. To prevent relapse, long-term oral steroids and immunosuppressive agent were administered. Conclusions: CLIPPERS may present as APS, and should be considered in the differential diagnosis of NMOSD.